Sustainable watershed management SuWaMa 2014 conference proceedings - Gönenç, I. Ethem; Wolflin, John P.; Russo, Rosemarie C. (CRC Press, 2014)
This proceedings volume contains papers and extended abstracts presented at the International Conference on Sustainable Watershed Management (SuWaMa 2014). The Conference was the second in a series of Sustainable Watershed Management Conferences. The objective of the Conference Series was to present and discuss advanced environmental models and contemporary decision support tools for the sustainable use and development of watersheds. Contributions cover the following topics: sound watershed management practices (case studies and examples from various countries including lessons learned from im.